2012
DOI: 10.1158/0008-5472.can-11-3983
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin Represses Basal and Cigarette Smoke–Induced Expression ofABCG2and Inhibits Stem Cell Signaling in Lung and Esophageal Cancer Cells

Abstract: Cigarette smoking at diagnosis or during therapy correlates with poor outcome in patients with lung and esophageal cancers, yet the underlying mechanisms remain unknown. In this study, we found that exposure of esophageal cancer cells to cigarette smoke condensate led to up-regulation of the xenobiotic pump ABCG2, which is expressed in cancer stem cells and confers treatment resistance in lung and esophageal carcinomas, and increased the side population of lung cancer cells containing cancer stem cells. Upregu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 48 publications
3
81
1
1
Order By: Relevance
“…MYC and KRAS activate a variety of pathways facilitating initiation and progression of lung cancer (24,48), and overexpression of these oncogenes correlates with treatment resistance and poor survival in lung cancer patients (49,50). Collectively, these observations strongly suggest that epigenetic repression of miR-487b enhances stemness phenotype of lung cancers and are consistent with our recent studies demonstrating that cigarette smoke upregulates ABCG2, increases pluripotent side population, and activates a variety of stem cell signaling pathways in lung cancer cells (51). Additional studies using gene expression profiling and flow cytometry techniques are in progress to more comprehensively examine the effects of miR-487b on global gene expression and stem cell phenotype of lung cancer cells and to more precisely define the constituents of cigarette smoke that induce stemness during pulmonary carcinogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…MYC and KRAS activate a variety of pathways facilitating initiation and progression of lung cancer (24,48), and overexpression of these oncogenes correlates with treatment resistance and poor survival in lung cancer patients (49,50). Collectively, these observations strongly suggest that epigenetic repression of miR-487b enhances stemness phenotype of lung cancers and are consistent with our recent studies demonstrating that cigarette smoke upregulates ABCG2, increases pluripotent side population, and activates a variety of stem cell signaling pathways in lung cancer cells (51). Additional studies using gene expression profiling and flow cytometry techniques are in progress to more comprehensively examine the effects of miR-487b on global gene expression and stem cell phenotype of lung cancer cells and to more precisely define the constituents of cigarette smoke that induce stemness during pulmonary carcinogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…The standard dose of mitoxantrone in humans (10-14 mg/m 2 ) produces peak plasma concentrations in the range of 1.0 mmol/L (30-32), but high-dose regimens using up to 80 mg/m 2 have been tested extensively and have been deemed safe (33). In summary, these results demonstrate that mithramycin A and mitoxantrone exert their antineoplastic activities in GIST cells at concentrations that are relevant for the clinic and can be achieved in the sera of patients with cancer (32,34).…”
Section: A Compound Screen Identifies Inhibitors Of Transcription Andmentioning
confidence: 99%
“…7 MIT was found to reduce drug resistance through downregulation of the xenobiotic pump ABCG2 and the multidrug resistant gene MDR1. 8,9 It was also shown that MIT inhibited DNA methyltransferase (DNMT), histone deacetylase (HDAC), and antiapoptotic protein XIAP. [10][11][12] Preclinical studies demonstrated that MIT can inhibit the generation and progression of several cancers, including carcinomas of the lung, breast, pancreas, stomach, and prostate, as well as sarcoma and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Preclinical studies demonstrated that MIT can inhibit the generation and progression of several cancers, including carcinomas of the lung, breast, pancreas, stomach, and prostate, as well as sarcoma and glioblastoma. 8,[13][14][15][16] Meanwhile, its prominent in vitro and in vivo activities linked to specific transcription regulation have triggered the clinical trials of MIT in lung cancer, esophagus cancer, and Ewing sarcoma, sponsored by the National Cancer Institute (NCT01610570, NCT01624090, and NCT02859415, www.ClinicalTrials.gov).…”
Section: Introductionmentioning
confidence: 99%